An Exploration of the Bystander Impact on Primary Students during Cooperative Group Work in the United Arab Emirates Schools - SHEIKH, NORA NOUR (2022)
The study is based on a mixed-method analysis of the bystander effect impact on primary students working in cooperative group work in the context of the United Arab Emirates. Nowadays, education has changed and drifted from standard teaching to online with the restrictions of social distancing. The reason behind this is the COVID-19 pandemic. The literature review clearly shows the facets that influence the students’ behaviour while working in groups—moreover, the challenges faced by the primary students and how to avoid and overcome those challenges resulting in avoiding the bystander effect. The research methodology section delivers proper strategies and design to conduct the research. The researcher used two tools in this study, the survey for students in upper primary to answer and the interview for the teachers. The data findings and analysis section clearly represent data gathered from the students all over the Emirates focusing on Dubai. The information collected from the students’ questionnaire is interpreted and analysed through SPSS software and provides deep analysis. The data gathered for the interview is examined with the support of the qualitative data analysis technique. The research study is significant as it covers the bystander effect on primary students, providing recommendations for future and further research